Penaksiran Risiko Korosi Beton Bertulang pada Bangunan Masjid Baitussalam dan Darul Makmur - Fonna, Syarizal; Furqan, M. Restu; Huzni, Syifaul (universitas teuku umar, 2023)
This study aims to assess the corrosion risk level of Baitussalam Mosque in Tibang Village and Darul Makmur Mosque in Lambaro Skep, Banda Aceh. The corrosion potential value is measured using a Half-Cell Potential Meter and visualized using VisIt software. The Profometer 5+ instrument is used to locate the reinforcement and tendons in the reinforced concrete construction. The corrosion risk level is determined based on ASTM C876 standards. The corrosion mapping results show that the northern side of Baitussalam Mosque in Tibang Village, Banda Aceh, is in a severe corrosion risk level, and the southern side of Darul Makmur Mosque is in a low to high corrosion risk level. Therefore, Baitussalam Mosque and Darul Makmur Mosque require further assessment to prevent building failure caused by corrosion.